Literary Lessons. Knowledge and Genre in Dutch Middlebrow Fiction of the Interwar Years - Bram Lambrecht; Pieter Verstraeten; Dirk de Geest (Belphégor)
The middlebrow novel has often been characterized as a highly didactic and pedagogical literary form, that aims to combine entertainment with education and instruction. In reaction to the often rather generalizing accounts of the middlebrow novel’s pedagogical function, this essay wants to sort out the different types of knowledge that can be involved and the different narrative and rhetorical means that are used to communicate these literary lessons. Focusing on two bestselling Dutch-language middlebrow novels from the interwar years – Whitey by Ernest Claes and Rubber by Madelon Székely-Lulofs – it is shown how different novelistic genres – the rural novel and the colonial novel – are almost naturally associated with different kinds of knowledge, but nevertheless display remarkably similar pedagogical strategies and techniques.